Transformation of Indonesian Army Personnel to Produce Experts Soldiers in the Field of Technology - Sahary, Fitry Taufiq; Mutaqin, Rizal; Mutaqin, Ghani; Dharmopadni, Dwi Shinta (Jurnal Pertahanan: Media Informasi tentang Kajian dan Strategi Pertahanan yang Mengedepankan Identity, Nasionalism dan Integrity, 2023)
The development of a fast-moving and dynamic strategic environment has an impact on the increasing situation of tension between countries. The visible phenomenon is the atmosphere of increasing the strength of the Armed Forces in regional countries (Arms Race) which then makes the threat dimension increasingly multipolar. On the other hand, the regional security situation, especially in Indonesia, is characterized by an increase in terrorism activities and other dangerous additives (Drugs) into the country, and boundary disputes related to the struggle for the use of increasingly massive natural resources. Flowing from the development of the strategic environment that gave birth to the complexity of threats to the sovereignty and integrity of the Republic of Indonesia. The study objective of this research is to provide advice to the leadership of the TNI AD regarding the transformation of TNI AD personnel development. So that this research uses the method of direct observation of the field. Besides observation, this research also uses the literature study method. Based on research results, obtained research results in the form the Army's personnel development has not been able to answer the dynamics of the strategic environment, the nature of threats, and organizational needs. Thus, it is necessary to make arrangements, especially in the recruitment system, education, and career development.